2019
DOI: 10.1152/ajplung.00502.2018
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in emphysema using a murine antisense oligonucleotide model of α-1 antitrypsin deficiency

Abstract: α-1 Antitrypsin (AAT) deficiency is the leading genetic cause of emphysema; however, until recently, no genuine animal models of AAT deficiency existed, hampering the development of new therapies. This shortcoming is now addressed by both AAT-null and antisense oligonucleotide mouse models. The goal of this study was to more fully characterize the antisense oligonucleotide model. Both liver AAT mRNA and serum AAT levels were lower in anti-AAT versus control oligonucleotide-treated mice after 6, 12, and 24 wk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In accordance with recent studies 29,30,32,34,58 , overexpression of circulating PCSK9 led to reduced LDLR, which was accompanied by increased LDL and cholesterol concentrations in plasma and vice versa. In addition to this, we also observed sex dependent differences in serum/plasma levels of alpa-1-antitrypsin (male > female), LDL (female > male) and PCSK9 in control mice in accordance with the literature [59][60][61][62][63][64] . This distinction was still visible in AAT plasma levels despite a general 1.6-fold increase after overexpression.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with recent studies 29,30,32,34,58 , overexpression of circulating PCSK9 led to reduced LDLR, which was accompanied by increased LDL and cholesterol concentrations in plasma and vice versa. In addition to this, we also observed sex dependent differences in serum/plasma levels of alpa-1-antitrypsin (male > female), LDL (female > male) and PCSK9 in control mice in accordance with the literature [59][60][61][62][63][64] . This distinction was still visible in AAT plasma levels despite a general 1.6-fold increase after overexpression.…”
Section: Discussionsupporting
confidence: 91%
“…In 2016, Tam et al ( 265 ) reported that smoke-induced COPD is characterized by small airway remodeling in female but not male mice and that ovariectomy before smoke exposure ameliorates the disease. Another study focusing on α-1 antitrypsin deficiency, the leading genetic cause of emphysema, also uncovered a higher susceptibility of female mice for this condition ( 266 ). However, these studies did not determine if androgens mediate resistance to COPD, or if the key to the observed sex differences is ovarian sex hormones.…”
Section: Effects Of Androgen Exposure On Monocytes and Macrophages Inmentioning
confidence: 99%
“…Proteins with the highest inter-replicate variability contain primarily metabolic (i.e., CPT1B, SCP2, ECI2, FABP5, BLVRB, and UQCRH) and protease modulating components (i.e., SERPINA1A, SERPINA3K, and SERPINA1D). Of the top 20 most variable proteins, 11 have been previously shown to be sexually dimorphic or regulated by sex hormones, including SCP2, SERPINA1A, , A1BG, SERPINA3K, FHL1, FABP5, LIFR, CDH2, CAND1, UQCRH, and SERPINA1D . Thus, it is likely that some of the inter-replicate variation observed in these proteins is due to sex-based biological differences.…”
Section: Resultsmentioning
confidence: 99%